Penilaian Aset Tetap Pada Pemerintah Daerah Kabupaten Lombok Utara - Rusli Amrul; Rusdi Rusdi (Valid: Jurnal Ilmiah, 2020)
This study aims to determine the valuation of fixed assets damaged by the earthquake in the Government Office of Population and Civil Registry Departement of North Lombok Regency. Data analysis used in this research is descriptive analysis method by collecting data, grouped and then arranged so that can be investigated based on relevant theories relating to the problem discussed by describing the situation or a phenomenon in the form of quantitative and qualitative data. The results of this study are fixed assets removed from the balance sheet by calculating the valuation of equipment assets that are eliminated in the financial statements in the balance sheet as of December 31, 2018 ie equipment is credited so that it automatically removes equipment assets in the balance sheet. Accumulated Depreciation and Deficit for equipment removal is recorded in the Operational Report (LO) as of December 31, 2018 and is an operating expense and reduces operating income. The valuation of office building assets that are eliminated from the financial statements in the balance sheet as of December 31, 2018, namely Office Buildings is credited so that it automatically deletes the Office Building Assets in the balance sheet. Accumulated Depreciation and Deficit for write-off of office buildings are recorded in the Operational Report (LO) as of December 31, 2018 and become an operating expense to reduce operating income